Двигуни зі змінною ступінню стиску - Коляса, Остап; Коляса, Андрій; Хома, Віталій (Видавництво Львівської політехніки, 2018)
Variable compression ratio is a technology to adjust the compression ratio of an internal combustion engine while the engine works. It is done to increase fuel efficiency under varying loads. Higher loads require lower ratios to be more efficient and vice versa. Variable compression engines allow to change the volume above the piston at 'Top dead point'. For automotive use it needs to be done dynamically according to the load and driving demands.
Engines with variable compresion ratio
Keywords: 629.03